Do the International Competencies of the Sports Physical Therapist need Updating? - Jo Verschueren; Maria Constantinou (International Journal of Sports Physical Therapy)
In 2005, the International Federation of Sports Physical Therapy (IFSPT) published the Sports Physiotherapy for All project (SPA)(1) which defined four key Roles and 11 Competencies a sports physical therapist should have, setting the standards for international education ever since. The aim of this international perspective is to reflect on the IFSPT competencies of a sports physical therapist and explore the need for an update.